Algorithms for Isotropy Groups of Cox-regular Edge-bipartite Graphs - Kasjan, Stanisław; Simson, Daniel (Fundamenta informaticae, 2015)
This paper can be viewed as a third part of our paper [Fund. Inform. 2015, in press]. Following our Coxeter spectral study in [Fund. Inform. 123(2013), 447-490] and [SIAM J. Discr. Math. 27(2013), 827-854] of the category ℬ i g r n of loop-free edge-bipartite (signed) graphs Δ, with n ≥ 2 vertices, we study a larger category ℛ ℬ i g r n of Cox-regular edge-bipartite graphs Δ (possibly with dotted loops), up to the usual ℤ-congruences ∼Z and ≈Z. The positive graphs Δ in ℛ ℬ i g r n , with dotted loops, are studied by means of the complex Coxeter spectrum s p e c c Δ